Discrepancies in resistant starch and starch physicochemical properties between rice mutants similar in high amylose content - Luo, Mingrui; Gong, Wanxin; Zhang, Siyan; Xie, Lanyu; Shi, Yitao; Wu, Dianxing; Shu, Xiaoli (Frontiers in Plant Science, 2023)
The content of resistant starch (RS) was considered positively correlated with the apparent amylose content (AAC). Here, we analyzed two Indica rice mutants RS111 and Zhedagaozhi 1B similar in high AAC and found that their RS content differed remarkably. RS111 had higher RS3 content but lower RS2 content than Zhedagaozhi 1B, correspondingly, cooked RS111 showed slower digestibility. RS111 had smaller irregular and oval starch granules when compared with Zhedagaozhi 1B and the wild type. Zhedagaozhi 1B showed a B-type starch pattern, different from RS111 and the wild type which showed A-type starch. Meantime, RS111 had more fa and fb1 but less fb3 than Zhedagaozhi 1B. Both mutants showed decreased viscosity and swelling power when compared with the parents. RS111 had the lowest viscosity and Zhedagaozhi 1B had the smallest swelling power. The different fine structures of amylopectin between RS111 and Zhedagaozhi 1B led to different starch types, gelatinization properties, paste viscosity and digestibility. Besides enhancing amylose content, modifications on amylopectin structure showed great potent in breeding rice with different RS2 and RS3 content, which could meet the increasing needs for various rice germplasms.